Analisis Tindak Tutur Asertif pada Tayangan YouTube iNEWS Debat Calon Wakil Presiden Pemilu 2024 serta Pemanfaatannya sebagai Bahan Ajar Teks Debat di SMA - Safira, Safira; Meliyawati, Meliyawati (Universitas Mathla'ul Anwar Banten, 2024)
This research aims to describe the form of assertive speech on the iNEWS YouTube show of the 2024 vice presidential election candidate debate as a learning material in high school. The research method used in this study is a qualitative descriptive method. The data source used in this study is iNEWS YouTube shows. The data collection technique uses the free viewing technique and the note-taking technique. The data analysis technique in this study uses descriptive analysis techniques. Based on the results of the analysis and discussion, in the first debate and the two vice presidential candidates for the 2024 election, 96 forms of assertive speech were produced, 63 speeches were made in the first debate of the vice presidential candidate, divided into 18 assertive speech acts, 9 assertive speech acts proposing, 5 assertive speech acts boasting, 12 assertive speech acts complaining, 8 assertive speech acts expressing opinions, and 11 acts of assertive speech reported. There were 33 speeches on the broadcast of the debate of the two vice presidential candidates, also divided into 5 acts of assertive speech stating, 3 acts of assertive speech proposing, 8 acts of assertive speech boasting, 4 acts of assertive speech complaining, 4 acts of assertive speech expressing opinions, and 9 acts of assertive speech reporting. From this analysis, it can be concluded that in this study, assertive speech acts stated and reported more were found, namely assertive, stated that there were 23 data, and assertive, reported, there were 20 data. Furthermore, the results of this analysis are implemented as teaching materials for debate texts in class X of high school.